Sosialisasi Kesehatan Gigi Dan Cara Merawat Gigi Pada Siswa-Siswi SDN 010 Desa Pangkalan Serik - Dian Oktary; Sukrul Yasir Al Qhofahri; Dian Maharani; Amina Yusra; Wulandari W; Bimbi Pramudya; Suci Maharani; Deflin Velicia; Anisa Dewi Humaira; Rafif Basyaair Herman; Qeissa Hudiev (Yayasan Daarul Huda Kruengmane, 2023)
In this Real Work Lecture program, we have realized one of the Tri Dharmas of Higher Education, namely community service. Apart from realizing one of the three great dharmas of higher education, we also implement one of the functions of students themselves, namely (agent of change). We carry out many activity programs in Pangkalan Serik Village. This activity program covers the educational sector, such as providing outreach to schools and we also contribute to teaching and learning activities. In the social sector, we actively participate in socializing with the community by taking part in community activities such as posyandu activities, gymnastics, rewang, and religious activities such as wirid and reciting the Koran. Apart from that, we also take part in training elementary school children to play drumband instruments and train young and young paskibras in celebrating the independence day of the Republic of Indonesia. The aim of implementing this program is so that students, namely ourselves, can receive a lot of experience and knowledge through direct participation in society and can apply it in their future lives.